STUDI TENTANG MANAJEMEN PRASARANA OLAHRAGA DI STADION KANJURUHAN KABUPATEN MALANG - Adi, Hardian Pamungkas; Adi, Sapto; Raharjo, Slamet (Jurnal Sport Science, 2017)
Abstract :Theobjective of this research is to find out the management ofKanjuruhan stadium sports infrastructure based on four process of management function; planning, organizing, actuating and controlling. The research uses qualitative descriptive approach, data collection technique through observation, interview, and documentation. Planning to create a work program every year, organizing learning from a good organizational structure, the implementation is done directly from DISPORA down to the field section, supervision of sports infrastructure management supervised by the inspectorate of District Government and BPKP. Conclusions from the results of the stadium management research have the process of management of sports infrastructure.Keywords :management, sport infrastructure, Kanjuruhan stadium.